Analyzing complex appraisals for business professionals - Pratt, Shannon P.; Lifflander, John (McGraw-Hill, 2016)
The essential guide to business and real estate appraisals for non-appraiser professionals In Analyzing Complex Appraisals for Business Professionals, renowned business and real estate valuation authorities Shannon P. Pratt and John Lifflander provide the ultimate crash course for evaluating a wide range of properties and enterprises. This guide to understanding, interpreting, and evaluating residential, commercial, business, and industrial appraisals, gives any business professional straightforward, practical steps to achieve sound financial reasoning in the face of numerous valuation intricacies and problem areas. Using a similar approach to Pratt's previous international bestselling books, the authors' detailed instructions and invaluable insider's advice make even the most sophisticated techniques accessible to bankers, attorneys, loan officers, accountants, real estate brokers, and other professionals. The authors introduce a strategic overview of the basics aspects of USPAP (Uniform Standards of Professional Appraisal Practice), and then build on that background. Each segment of the book includes a discussion of the applicable appraisal theory, which is then followed by an explanation of the most common methodologies for that particular discipline and a set of examples of its application. Analogies with general concepts are also applied to specific appraisal subjects. The ability to evaluate a wide range of properties and enterprises?from land and homes to commercial and industrial facilities to valuations of businesses?is more imperative today than ever before. Find out why, and the best practices to do so, with Analyzing Complex Appraisals for Business Professionals. --Provided by publisher.